2012
DOI: 10.3354/meps09833
|View full text |Cite
|
Sign up to set email alerts
|

Nursery origin of yellowfin tuna in the Hawaiian Islands

Abstract: Stable isotopes of carbon (δ 13 C) and oxygen (δ 18 O) in otolith cores (first 2 mo of age) of young-of-the-year (YOY) yellowfin tuna Thunnus albacares were used as natural tracers to predict the nursery origin of sub-adults (age-1) collected from the Hawaiian Islands. YOY fish were first collected from nurseries throughout the western and central Pacific Ocean (WCPO) to determine whether δ 18O otolith relative to other regions. Inter-annual variability in otolith core chemistry was minor and only observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 30 publications
(14 reference statements)
6
43
3
Order By: Relevance
“…This is broadly in line with the results in Grewe et al. (), who identified three populations in the Pacific Ocean and also from Wells, Rooker, and Itano () who, through otolith chemistry data, showed that Hawaiian yellowfin are likely to form their own stock. There are differences between methods though, with the structure and the admixture models having a less clear signal.…”
Section: Stock Structure Of Yellowfin Tunasupporting
confidence: 91%
“…This is broadly in line with the results in Grewe et al. (), who identified three populations in the Pacific Ocean and also from Wells, Rooker, and Itano () who, through otolith chemistry data, showed that Hawaiian yellowfin are likely to form their own stock. There are differences between methods though, with the structure and the admixture models having a less clear signal.…”
Section: Stock Structure Of Yellowfin Tunasupporting
confidence: 91%
“…Similar to Wells et al . (), the template was constructed using otolith measurements from the smallest individuals [≤ 25 cm fork length (FL)] in our sample of each species, which represented core material accreted during the first ~3 months of life. The final milling template was the same for T. obesus and T. albacares, and a series of drill passes was run over the preprogrammed milling template using a 500‐ μ m‐diameter Brasseler carbide bit (Brasseler USA, Medical L.L.C., Ventura, CA, USA) until a depth of approximately 800 μ m was reached.…”
Section: Methodsmentioning
confidence: 99%
“…O to determine the natal origin or environmental history of pelagic fishes, including tunas, is well established (Rooker et al 2008a, Wells et al 2012). Both of the markers used in the present study are particularly suitable for investigating the origin and movement of highly migratory fishes because latitudinal and longitudinal differences in seawater δ 13 C and δ…”
mentioning
confidence: 99%